Stock price crash risk: evidence from China - Wang, Meng (2021)
This thesis presents three closely related empirical studies which examine, in separate working paper format, important yet understudied determinants of stock price crash risk: trade credit provision, debt and financial assets investment. Drawing from agency theory, particularly, the role of information transparency and "bad news hoarding" under the Chinese emerging markets setting, we document some distinctive patterns from a large sample of Chinese firms which strongly support our predictions. First, we find that trade credit provision significantly increases stock-price crash risk which consistent with our hypotheses that customer-supplier economic links through trade credit facilitate bad news hoarding. Second, we find that debt financing decreases stock price crash risk. This finding supports our prediction that creditors play an effective monitoring role in China's weak informational environment consequently constraint bad news hoarding. Last but not least, we show that firms investing less in capital assets hold more financial assets. Stock price crash risk decreases with financial assets investment and increases with capital investment. These findings support the view that for firms with severer agency problems, capital investment increases agency costs and facilitate bad news hoarding, whereas financial assets investment reduces firm information asymmetry due to better information transparency.